2003
DOI: 10.1088/0953-8984/15/50/007
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelastic phase transition in K3Na(CrO4)2single crystals: an electron paramagnetic resonance study

Abstract: The phase transition in K3Na(CrO4)2 single crystals has been studied by electron paramagnetic resonance (EPR) of Mn2+ ions. The values of the spin-Hamiltonian parameters have been evaluated. Below the phase transition temperature, the magnetic z-axis is deflected in ac and bc crystallographic planes by the same angle. Anomalous line shapes recorded below the phase transition temperature suggest the existence of an incommensurate phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…This limitation has been circumvented by experiments employing strong external magnetic fields, yielding a coherence time of 1.3 seconds for hyperfine transitions in 167 Er 3+ :Y 2 SiO 5 11 , and thus demonstrating the practical viability of quantum memories at 1.5 µm. In order to guide such developments using accurate theoretical models, in addition to enabling the above outlined ZEFOZ technique, it is crucial to have an accurate understanding of the hyperfine structure of Er doped yttrium orthosilicate [12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…This limitation has been circumvented by experiments employing strong external magnetic fields, yielding a coherence time of 1.3 seconds for hyperfine transitions in 167 Er 3+ :Y 2 SiO 5 11 , and thus demonstrating the practical viability of quantum memories at 1.5 µm. In order to guide such developments using accurate theoretical models, in addition to enabling the above outlined ZEFOZ technique, it is crucial to have an accurate understanding of the hyperfine structure of Er doped yttrium orthosilicate [12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…EPR studies of the KNCr crystals [11] suggested an incommensurate phase transition between 228 K and 238 K. The KNS, which is isostructural with KNCr, revealed the incommensurate-like behaviour between T 1 and T 2 . Preliminary X-ray scattering studies in KNS [12] revealed both doubled value of c parameter below T 1 and satellite reflexes between T 1 and T 2 .…”
Section: Discussionmentioning
confidence: 94%
“…The proper ferroelastic K 3 Na(CrO 4 ) 2 is an object of intense interest and extended studies have been carried out [1][2][3][4]. The main aim of these works, including the X-ray diffraction [1], EPR -and acoustic spectroscopy studies [2,3] was mainly the investigation of the nature and properties of a weak first-order proper ferroelastic phase transition (T c = 239 ).…”
Section: Introductionmentioning
confidence: 99%
“…The main aim of these works, including the X-ray diffraction [1], EPR -and acoustic spectroscopy studies [2,3] was mainly the investigation of the nature and properties of a weak first-order proper ferroelastic phase transition (T c = 239 ). The ultra-sound study of K 3 Na(CrO 4 ) 2 and the theoretical analysis showed [3] that the primary order-parameter η 1 and the derived one -η 2 are defined by the components of strain tensor ε 4 and (ε 2 -ε 1 )/2, respectively in this case.…”
Section: Introductionmentioning
confidence: 99%